ID 319 – Is the presence of late evoked potentials (N100 wave) a good predictor of survival in comatose patients?. Issue 3 (March 2016) - Souci, S.; Bastuji, H.; Garcia-larrea, L.; Andre-obadia, N.
Abstract : Objective: The persistence of both early cortical responses (N20, Pa) and late associative potentials (vertex potentials, N100) has been shown to improve the probability of return to consciousness of comatose patients. However, the prognostic value of late responses without early cortical potentials has not been documented. Methods: We report results in 5 comatose patients in whom late N100 responses could be recorded in the absence of reproducible early cortical auditory and/or somatosensory potentials. The etiologies of coma were: anoxic–ischemic after cardiopulmonary arrest (3), brainstem hemorrhage (1) and ischeamic stroke (1). Results: All patients showed reproducible N100 waves but absence of early cortical auditory and/or somatosensory responses. The EEG was non-reactive in 3 patients. All 5 patients had a poor clinical outcome, toward either death or vegetative state. Discussion: The presence of N100 wave without previous recordable potentials may be explained either by alternative parallel pathways, or by re-synchronization of an altered ascending volley. Whatever the explanation, the presence of N100 wave may be associated with a good neurological outcome only if preceded by early cortical potentials (Pa and N20), but not if early responses are absent. Key message: Caution should be exerted in interpreting the prognostic value of the N100 wave alone.